Playing God in Nigerian political experience: towards a christian responsibility - Igboin, Benson Ohihon (Creativity Studies, 2013)
The Nigerian universe is a religious one; all phenomena and experiences are apparently explained in the supernatural. It is in this sense that religion and politics are inseparable, though ambidextrous. In this sense, the theoretical or constitutional separation thesis differs from the apodictic demonstrative reality. The latter form of this relationship attributes all events to acts of God, whether good or evil, but more evil than good. The act, will or grace of God (Insha’Allah) in the Nigerian political experience, in the assessment of Christian principles, calls for an evaluation of the political and politicians’ recourse to God in the face of anti-God and anti-people display of political power. It is the argument of this paper that God is an alibi in Nigerian political development, thus making the political system to play God. Through the gristmill of critical analysis, it is argued that Christian eligible voters in a democracy bear crucial responsibility of not only correctly and critically, in a contextual manner, interpreting the scriptures, but also going beyond prayer for leadership, which source and ascendancy to power is questionable and illegitimate. The Christian responsibility must therefore be comprehensive, authentic and pragmatic. Dievo vaidmuo Nigerijos politiniuose potyriuose: link krikščioniškosios atsakomybės Santrauka. Nigerijos pasaulis yra religinis: visi reiškiniai ir potyriai akivaizdžiai aiškinami antgamtiškumu. Šia prasme religija ir politika yra neatskiriamos, tačiau dviveidės. Tad teorinio ar konstitucinio atsidalijimo tezė skiriasi nuo apodiktinės akivaizdžios realybės. Pastaroji šio santykio forma visus įvykius priskiria Dievo veiklai, – tiek gėrį, tiek ir blogį, tačiau labiau blogį nei gėrį. Išanalizavus krikščionybės principus, Nigerijos politiniame gyvenime Dievo (Insha’Allah) veikla, valia ar malonė antdievo bei antžmoniu, demonstruojančių politinę galią, akivaizdoje kviečia įvertinti politikos ir politikų atsigręžima į Dievą. Šiame straipsnyje argumentuojama, kad Dievas yra Nigerijos politinės raidos alibi, verčiantis politinę sistemą vaidinti Dievą. Pasitelkiant griežtą kritinę analizę, įrodinėjama, kad tinkami rinkėjai demokratijos sąlygomis yra atsakingi ne tik korektiškai ir kritiškai, kontekstualiu būdu interpretuodami šventuosius raštus, bet taip pat ir dėl vadovavimo, kurio šaltinis ir įtaka valdžiai yra abejotini ir neteisėti. Todėl krikščioniškoji atsakomybė turi būti visapusė, autentiška ir pragmatiška. Reikšminiai žodžiai: demokratija, krikščioniškoji atsakomybė, politika, galia, religija, Dievas, teologas. First published online: 31 Dec 2013